Metaphorical Analysis and the Meaning of Song “Another One Bite the Dust” By Queen - Zulaika, Adristi Yajna; Artanti, Chairinnisa; Alivia, Cut Putri; Annisa, Dira; Putri, Dian Marisha (Journal of Linguistics, Literacy, and Pedagogy, 2023)
A metaphor is a figure of speech that contrasts two unrelated items and helps communicate complex ideas or emotions by drawing on familiar or concrete concepts. Metaphor is often utilized in poetry, novels, films, songs, etc. This study provides a metaphorical analysis of the lyrics of